Ventral Caudate and Anterior Insula Recruitment During Value Estimation of Passionate Rewarding Cues - Duarte, Isabel Catarina; Coelho, Gonçalo; Brito-Costa, Sónia; Cayolla, Ricardo; Afonso, Sónia; Castelo-Branco, Miguel (Frontiers in Neuroscience, 2020)
‘Wanting’, a component of the reward processing, is a motivational property that guides decision making in goal-oriented behavior. This includes behavior aiming to support relational bonds, even at the group level. Accordingly, group belongingness works as this motivational property, which is fundamentally different from romantic or maternal love. While primary rewards (or learned associations, as money) have been largely used to study the conceptual framework associated ‘wanting’, other cues triggering behavior, as passionate motives, are less studied. We investigated the neural correlates of value estimation of passion-driven incentive in neuropsychologically defined football fans. We asked the participants (n=57) to compute the value of football tickets (the cues that trigger passionate behavior in this “tribal love” context). The trials were all different, comprising tickets for different matches. The participants had no restrictions to the amount to be introduced. This enabled a parametric fMRI design based on the explicit estimated value given by the participants, in a trial by trial approach. In a whole brain approach (to prevent biased focus on value related regions), only the activity in ventral caudate and left anterior insula showed a critical relationship with the reported value. Higher normalized values led to larger activity in the striatum and left insula. The parametric map shows that these regions encode the magnitude of incentive by indexing self-relevant value. Other regions were involved is value computation as the ventromedial prefrontal cortex, lateral orbitofrontal cortex and the dorsolateral prefrontal cortex, but did not exhibit parametric patterns. The involvement of the nucleus accumbens in value estimation was only found in ROI based analysis, which emphasizes the role ventral caudate for the presently studied social “reinforcer” cue.